PEMBIAYAAN PENDIDIKAN BERBASIS POTENSI UMAT Analisis School Levy - Umi Zulfa (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
School levy is a concept that can be used as an alternative model which is applied in education funding management practices, particularly in searching for additional sources of financing education. The basic concept of school levy is financing of school education supported by property taxes. Property tax is the property tax paid by people who have a relative excess/wealth. These people, in Islam belong to the group of people who are obliged to pay zakat. The core of school levy is funded by the public school which is in Islam, similar to the financing of education taken from the people in the form of the potential payment of zakat, infak, sadakah, waqf (Ziswa) and the like. Applying school levy model helps the education funding issues that still have not been sufficiently overcome yet by empowering Muslims which basically has Ziswa concept. If this concept is managed properly, it will be an abundant source of education funding and be available continuously.